Cellular sources of IL-17 in psoriasis: a paradigm shift? - Keijsers, Romy R. M. C.; Joosten, Irma; van Erp, Piet E. J; Koenen, Hans J. P. M.; van de Kerkhof, Peter. C. M. (Experimental dermatology, 2014)
Psoriasis is a common chronic inflammatory skin disease that results from interplay between the immune system and the epithelium. In the light of very successful anticytokine therapies for psoriasis, the focus has been directed towards the adaptive immune system. Expression studies, genetic studies and treatments specifically targeting players of the IL‐23/IL‐17 pathway, point at an important role for IL‐17 in the pathogenesis of psoriasis. IL‐17 stimulates the keratinocytes to produce psoriasis‐associated molecules, eventually leading to chronic skin inflammation. The current opinion is that IL‐17 is mainly produced by T cells, so‐called T‐helper 17 (Th17) cells, in psoriasis. However, evidence is accumulating that cells of the innate immune system, like neutrophils, mast cells, γδ T cells and innate lymphoid cells are the main source of IL‐17 in psoriasis, rather than T cells. The paradigm in this field of research is shifting. With this viewpoint article, we will address this novel concept by critically summarizing the current literature on this subject. In psoriatic arthritis and atherosclerosis, important conditions related to psoriasis, it was also found that the majority of IL‐17 is associated with cells of the innate immune system. This new concept changes our view of IL‐17. Blocking IL‐17 with targeted treatments might be more far‐reaching than previously thought; not only IL‐17 production by T cells but also by innate immune cells is blocked. Furthermore, therapies specifically targeting IL‐17 may not only improve psoriasis, but also comorbidity that is associated with the IL‐17 pathway, hereby preventing serious complications on the long term.